Моделювання вібраційної динаміки переміщення дисперсійного матеріалу на конічній поверхні решета зерносепаратора - Котов, Б. І.; Степаненко, С. П.; Швидя, В. О.; Пастушенко, М. Г.; Kotov, Boris; Stepanenko, Sergey; Shvidy, Victor; Pastushenko, Nicholas (КНТУ, 2013)
В статті розглянута удосконалена математична модель вібраційного переміщення зерноматеріалу на конічному решеті з урахуванням зміни маси продукту в напрямку його руху. Objective - improving mathematical model material moving along a conical surface in the presence of harmonic oscillations by considering changes in the mass of grain on the sieve by sieving fraction part. Method for studies of the dynamics of a point, which simulates the rolling element layer of grain, the mathematical description of the vibrating particles moving along the grain of the material cone sieve that rotates around a vertical axis, while harmonically oscillating in the vertical direction. Particle moves on the surface of the rotor element up and down according to the vertical oscillation sieve. In this case, consider the motion of a particle along the axis ξ is the same as forming a conical surface and carries with it both rotational and vibrational motion for the harmonic law. Thus found that an increase in velocity of the screening rate decreases. In this paper the improved mathematical model of vibration displacement grain conical sieve material in the changing weight of the product in the direction of its movement. Conclusions: 1. Compiled mathematical model of a vibrating movement of grain on the conical surface of the rotor of a centrifugal separator based on the kinetics of screening throughput fraction of grain mixture. 2. Solution of the mathematical model makes it possible to determine the mass distribution of grains in a sieve and therefore the height of the layer of grain, which makes it possible to optimize the separator intensity of screening criteria.
Dynamic simulation of vibration on moving dispersive materials cone sieve separator
Keywords: вібраційна динаміка; дисперсійний матеріал; решето; зерносепаратор; vibrational dynamics; dispersion material; sieve; separator